Preventive Measures against Various Diseases of African Ostriches and Their Treatment - Troyanovskaya, Rano Abdusattarovna; Isakhmukhamedov, Salikh Shukurovich (International Journal on Integrated Education, 2023)
Recommendations for the prevention and treatment of various diseases found in African ostriches are given. The symptoms of diseases, causes and methods of their treatment are described. Timely detection of the disease and treatment will help to avoid death and economic loss.